Vagus nerve stimulation for bilateral temporal lobe epilepsy caused by fractionated radiation therapy: A case report - Yoko Matsuo (Elsevier, 2022)
Background: Mesial temporal lobe epilepsy (MTLE) is a disorder with an epileptogenic focus within the temporal lobe that generally involves a history of infantile “initial precipitating incidents.” Case description: We describe a rare case of radiation-induced bilateral MTLE. A 38-year-old woman underwent fractionated radiation therapy for tectal glioma at the age of 7 years. Subsequently, she experienced drug-resistant epileptic seizures. Based on the ictal semiology, image inspection, and electroencephalography, she was diagnosed with bilateral MTLE with left hippocampal sclerosis involving bilateral seizure foci. She underwent vagus nerve stimulation (VNS) surgery, which improved her seizures; specifically, her drop attacks completely stopped. Conclusions: To our knowledge, this is the first reported case of radiation-induced bilateral MTLE with left hippocampal sclerosis. VNS is considered as a good surgical treatment for certain cases of bilateral MTLE cases.